2011
DOI: 10.1177/201010581102000110
|View full text |Cite
|
Sign up to set email alerts
|

A Missing C-Spine Link: Mind the Gap

Abstract: A woman presented with metastatic breast cancer, having extensive lytic bony involvement of C2 vertebra and limited symptoms. We present the radiologic findings and case history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Speaking seven months after the parliamentary debates, he revealed that his government had been faced with intense resistance, if not outright opposition, to the Vandalism Act's mandatory corporal punishment from the government's own legal officers (Lee 1967). Lee's audience consisted primarily of private‐sector lawyers but included the state's elite legal actors—the chief justice, the High Court judiciary, the attorney general, and the speaker of Parliament (Tan 1967, xxxv). To this audience of Singapore's legal complex, Prime Minister Lee revealed that the attorney general, technically the highest‐ranking government legal officer in a Westminster system, had vigorously opposed the Vandalism Act:…”
Section: State Lawyers For Liberalismmentioning
confidence: 99%
“…Speaking seven months after the parliamentary debates, he revealed that his government had been faced with intense resistance, if not outright opposition, to the Vandalism Act's mandatory corporal punishment from the government's own legal officers (Lee 1967). Lee's audience consisted primarily of private‐sector lawyers but included the state's elite legal actors—the chief justice, the High Court judiciary, the attorney general, and the speaker of Parliament (Tan 1967, xxxv). To this audience of Singapore's legal complex, Prime Minister Lee revealed that the attorney general, technically the highest‐ranking government legal officer in a Westminster system, had vigorously opposed the Vandalism Act:…”
Section: State Lawyers For Liberalismmentioning
confidence: 99%